Understanding the COVID-19 vaccine uptake, acceptance, and hesitancy in Ethiopia and Tanzania: a scoping review - Gudina, Esayas Kebede; Muro, Florida Joseph; Kyala, Norman Jonas; Melaku, Tsegaye; Sørensen, Jane Brandt; Meyrowitsch, Dan Wolf; Mekonnen, Zeleke; Dræbel, Tania Aase (Frontiers in Public Health, 2024)
BackgroundThe development and implementation of COVID-19 vaccines have been a breakthrough in controlling the pandemic. However, the vaccination coverage in most low-income countries remains very low due to critical vaccine shortage and profound hesitancy. In this scoping review, we aimed to assess COVID-19 vaccine uptake, acceptance, and hesitancy in Ethiopia and Tanzania.MethodsThe search was made in PubMed, Scopus, Embase, and Web of Science. Only original research articles focusing on vaccine acceptance and hesitancy were included. The studies selected for a full read were analysed using a thematic analysis approach.FindingsA total of 76 articles were included in the study, with 74 of them coming from Ethiopia. The study found an increasing trend in vaccine uptake over time. However, there was also an increase in hesitancy and a decline in willingness to receive the vaccine. The willingness to receive the COVID-19 vaccine in Ethiopia ranged from 18.5 to 88%. The main reasons for "vaccine hesitancy" included fear of side effects, concerns about long-term safety, doubts about vaccine effectiveness, lack of information, vaccine fast-tracking, and religious beliefs. The study also found that younger individuals, females, and pregnant women were less willing to receive the vaccine. The adverse events reported among vaccinated individuals were mostly mild. Most of the studies operationalised vaccine acceptance-hesitancy as dichotomous variables. However, the historical, political, and socio-cultural context in which vaccine acceptance and hesitancy occur was not given any attention. While there is a good amount of data from Ethiopia describing patterns of vaccine acceptance and hesitancy among different populations over time, there is limited information from Tanzania due to the late arrival of the vaccine and limited published articles.ConclusionWe have observed a paradox involving two seemingly conflicting trends: an increase in vaccination rates/coverage and "anti-vax." Most studies have simplified vaccine acceptance-hesitancy as an “either-or” incident, without considering its dynamic nature and occurrence within a broader political, social, and cultural context. Therefore, it is crucial to explore approaches that can enhance our understanding of the vaccine acceptance-hesitancy phenomenon, in order to improve vaccine trust and uptake.